Citizens and states: considering the concept of citizenship - Hinchcliffe, C (2015)
This thesis is an investigation into the concept of citizenship, or, more precisely, the core concept of citizenship. It attempts to show how certain key debates within citizenship theory can (and should) be framed once the core concept has been clarified. Its central claim is that citizenship is primarily an institutional relationship between an individual and the laws and organs of government to whose authority she is subject. All other 'aspects', 'dimensions', 'senses', or conceptions of citizenship, should be oriented in relationship to this core meaning. Understanding citizenship as primarily an institutional relationship affects how we should approach a number of issues in citizenship theory. The first issue I consider has to do with the limits of both citizenship theory and the extension of citizenship in practice. Specifically, can the conceptual category of citizenship apply to non-human animals, or, indeed, for animals to be citizens in sense that is substantively on par with human citizens? I next consider what the core concept tells us about the moral aspect of citizenship and the relationship between co-citizens. I ask whether one’s membership in a morally bounded community could be either necessary or sufficient for a kind of citizenship, and whether citizens owe each other special obligations qua citizens. Finally I ask who might have a moral claim to citizenship in a given state. I consider the possible moral claims a person might have to each of citizenship’s two primary elements—what I call democratic membership (i.e. to be included in the demos of a democratically governed polity), and basic membership (i.e. the rights to live and work within the territory of a polity). The first sort of claim brings us into contact with the debate over what is known as the democratic boundary problem, while the second leads us to consider the practice of birthright ascription.